Pengaruh Perubahan Legheel Alignment terhadap Lordosis Lumbal pada Penderita Overweight Di Komunitas Senam Aerobik Blukid Sidoarjo - Rosse Tirta Sari; Ahmad Abdullah; Rachma Putri Kasimbara; Yohanes Deo Fau (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: The foot has two main functions, first as the foundation of the body (base of support) and second as a lever in advancing the body when walking or running. The arch of the foot or arcus pedis is one of the most important parts that affect biomechanics and musculoskeletals in the feet (Ozdinc, et al., 2016). The presence of structural and functional abnormalities in the feet can cause posture abnormalities in the legs, based on the structure of foot posture is divided into three types, namely normal arch, low arch / flat and high arch / cavus. (Mootaah et al,2014)Methods: This study using non-parametric statistical methods is a statistical method that can be used by ignoring assumptions that underlie the use of study results of treatment of leg hell alignment respondents obtained a value of p 0.00 (p < 0.05), which shows statistically the Effect of Leg heel Alignment Changes On Lumbar Lordosis In Overweight Sufferers In The Aerobic Gymnastics Community Blukid SidoarjoResults: With the change in the angle of leg hell alignment, it also affects the change in the angle of lumbar lordosis in aerobic gymnastics respondents in Bluru Kidul Sidoarjo. Conclusion: With the provision of insole and aerobic gymnastics is expected to be a solution related to handling if there are symptoms due to hyperlordosis from lumbar, especially in overweight sufferers, by also paying attention to the condition of leg heel alignment.